Tindak Tutur Ilokusi Searle dalam Musalsal an-Nabī Yūsuf aṣ-Ṣiddīq al-Ḥalqah al-Khāmisah ‘Asyar (Kajian Pragmatik): Searle's Illocutionary Speech Acts in Musalsal al-Nabī Yūsuf al-Ṣiddīq al-Ḥalqah al-Khāmisah ‘Asyar (Pragmatic Study) - Muhammad Haritsah Rais; Dayudin; Muhamad Naufal Rizky; Muhammad Fachri (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
In pragmatic studies, language is not only understood as a series of words, but also as an action that has a specific purpose, known as a speech act. One type of speech act that is important to study is the illocutionary act because it is directly related to the intention and function of the speaker's utterance. This study aims to describe the types and functions of illocutionary acts contained in Musalsal al-Nabī Yūsuf al-Ṣiddīq al-Ḥalqah al-Khāmisah ‘Asyar or the TV series of the story of the prophet Yusuf a.s episode 15 based on John Searle's classification. This study uses a qualitative approach with a descriptive method. The source of research data is the speech of the characters contained in the dialogue. The data collection technique is carried out using the listening and note-taking method, while the data analysis technique uses Searle's illocutionary speech act theory. The results of the study showed that there were 54 types of illocutionary speech acts in the episode, consisting of 17 assertive speech acts, 14 directive, 4 commissive, 7 expressive, and 2 declarative. Functionally, they include assertive speech acts such as conveying information, explaining, reporting, and claiming; directive speech acts such as ordering, requesting, recommending, and inviting; commissive speech acts involving the speaker's ability, such as offering, promising, and threatening; expressive speech acts that include expressing feelings, such as saying thank you, congratulating, praising, and apologizing; and declarative speech acts related to the act of deciding or making decisions. This study is confirms that understanding the function of speech in audiovisual media can help explain how Islamic messages are conveyed in a subtle, communicative, and meaningful way to listeners or viewers.